Sosialisasi Pengenalan Laporan Keuangan Sederhana dan Kewirausahaan untuk Meningkatkan Literasi Keuangan Bagi Generasi Z di SMK Satrya Budi Perdagangan - Syahilla Lubis; Enjela Kasmawati; Dinda Tri Jelita; Mutiah Khaira Sihotang (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This outreach program aims to increase financial literacy among Generation Z students at Satrya Budi Trade Vocational School through the introduction of simple financial reports and entrepreneurship. In the digital era which is characterized by easy access to information, understanding personal financial management and entrepreneurship is very important. This activity involves interactive presentations, financial recording simulations, and group discussions to provide hands-on experience to students. The evaluation results showed an increase in students' understanding of financial and entrepreneurship concepts, with participants being successful in answering evaluation questions well. With this program, it is hoped that students can develop the skills needed to manage finances and start a business in the future.